Physico-chemical characteristics of papaya (Carica papaya L.) seed oil of the Hong Kong/ Sekaki variety - Abdul Manaf Yanty, Noorzianna; Marikkar, Mohammed Nazrim; Nusantoro , Bangun Prajanto; Long , Kamariah; Mohd Ghazali , Hasanah (Japan Oil Chemists' Society, 2014)
A study was carried out to determine the physico-chemical characteristics of the oil derived from papaya seeds of the Hong kong/Sekai variety.Proximate analysis showed that seeds of the Hong Kong/ Sekai variety contained considerable amount of oil (27%). The iodine value, saponification value, unsaponifiable matter, free fatty acid content of the freshly extracted papaya seed oil were 76.9 g iodine / 100g of oil, 193.5 mg KOH/ 1 g of oil, 1.52%, and 0.91 %, respectively.